2005
DOI: 10.1245/aso.2005.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival Associated With Postoperative Wound Infection in Dogs Treated With Limb-Salvage Surgery for Osteosarcoma

Abstract: In dogs with osteosarcoma treated with limb-salvage surgery, infection has a positive influence on survival, as does a smaller initial length of radius involved and lower body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
136
5
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(158 citation statements)
references
References 62 publications
16
136
5
1
Order By: Relevance
“…Similar findings have been detected in canine osteosarcoma studies, suggesting an immune response may inhibit osteosarcoma tumors in vivo [10]. The production of tumor-specific humoral and cellular immune responses to osteosarcoma has been previously recognized, prompting interest in the potential role of immunotherapy in osteosarcoma [11,12].…”
Section: Immunotherapysupporting
confidence: 76%
“…Similar findings have been detected in canine osteosarcoma studies, suggesting an immune response may inhibit osteosarcoma tumors in vivo [10]. The production of tumor-specific humoral and cellular immune responses to osteosarcoma has been previously recognized, prompting interest in the potential role of immunotherapy in osteosarcoma [11,12].…”
Section: Immunotherapysupporting
confidence: 76%
“…Previously, nonspecific immune stimuli, such as spontaneous bacterial infections following limb sparing surgery (38,39) or liposome encapsulated muramyl tripeptides (L-MTP-PE) administered after amputation and platinum therapy have resulted in significant prolongation of metastasis-free interval (11.3 months vs. 7.6 months; control) and overall survival (14.4 months vs. 9.8 months; control) in dogs with osteosarcoma (37,38). Consequently, L-MTP-PE (mifamurtide; MEPACT) was evaluated in, and received approval for pediatric osteosarcoma in Europe in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…The sarcoma surgical literature has reported correlations between deep surgical infection and improved overall survival. In a study of 47 dogs with sarcoma, Lascelles et al found a correlation between survival and the clinical event of a deep surgical infection [11]. Additionally, a large study from the Royal Orthopaedic Hospital in Birmingham, England, showed a statistical (p=0.017) advantage to deep surgical infection in terms of long-term survival [12].…”
Section: Foundationsmentioning
confidence: 99%